Unmanned Aerial Vehicles for Three‑dimensional Mapping and Change Detection Analysis - Gbopa, Adetola Olufunmilayo; Ayodele, Emmanuel Gbenga; Okolie, Chukwuma John; Ajayi, Akinwumi Olaitan; Iheaturu, Chima Jude (Geomatics and Environmental Engineering, 2021)
Unmanned Aerial Vehicles (UAVs), commonly known as drones are increasingly being used for three‑dimensional (3D) mapping of the environment. This study utilised UAV technology to produce a revised 3D map of the University of Lagos as well as land cover change detection analysis. A DJI Phantom 4 UAV was used to collect digital images at a flying height of 90 m, and 75% fore and 65% side overlaps. Ground control points (GCPs) for orthophoto rectification were coordinated with a Trimble R8 Global Navigation Satellite System. Pix4D Mapper was used to produce a digital terrain model and an orthophoto at a ground sampling distance of 4.36 cm. The change detection analysis, using the 2015 base map as reference, revealed a significant change in the land cover such as an increase of 16,306.7 m2 in buildings between 2015 and 2019. The root mean square error analysis performed using 7 GCPs showed a horizontal and vertical accuracy of 0.183 m and 0.157 m respectively. This suggests a high level of accuracy, which is adequate for 3D mapping and change detection analysis at a sustainable cost.